2021
DOI: 10.1080/07853890.2021.1970217
|View full text |Cite
|
Sign up to set email alerts
|

P38 MAPK/AKT signalling is involved in IL-33-mediated anti-apoptosis in childhood acute lymphoblastic leukaemia blast cells

Abstract: Background Acute lymphoblastic leukaemia (ALL) is often characterized by broad clinical and biological heterogeneity, as well as recurrent genetic aberrations. Despite remarkable improvements in the treatment outcome in paediatric ALL over the past several decades, it remains a leading cause of morbidity and mortality among children. Cytokines have been extensively studied in haematologic diseases; however, the mechanisms by which cytokines contribute to ALL pathogenesis remain poorly understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…6 A). As a p38 MAPK inhibitor, SB203580 was reported to block Akt phosphorylation ( Wang et al, 2021 ). Herein, an obvious decrease in Akt 1/2/3 (S473) phosphorylation level was detected in KG1a cells upon the combination treatment, compared to DNR alone ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A). As a p38 MAPK inhibitor, SB203580 was reported to block Akt phosphorylation ( Wang et al, 2021 ). Herein, an obvious decrease in Akt 1/2/3 (S473) phosphorylation level was detected in KG1a cells upon the combination treatment, compared to DNR alone ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Stojak et al (2014) reported G2/M-phase arrest in human AML cell line ML-1 and human acute lymphoblastic leukemia (ALL) cell line MOLT-4 after treating the cells with 50 and 150 nM DNR for 72 h of incubation. Using two acute lymphoblastic leukemia (ALL) cell lines CCRF-CEM and MOLT-4 derived from T lymphocytes, DNR treatment was also reported to cause cell growth arrest in G2/M-phase, accompanied by increased levels of p53 and its target gene cell cycle inhibitor p21 ( Al-Aamri et al, 2019 , Wang et al, 2021 ). Both p53 and p21 indicate cell growth arrest and DNA damage due to intercalation of the DNR between DNA base pairs, causing DNA double-strand breaks and topoisomerase II inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The p38 MAPK signaling pathway enables the adroit interpretation and response to external signals, effectuating varied biological outcomes despite its ostensibly linear architecture. IL-33 markedly circumvents apoptosis via p38 MAPK and AKT pathway activation, a process antagonized by the p38 MAPK inhibitor, SB203580 [29] . This research unveils IL-33 promotion of inflammatory cytokines IL-6 and IL-8 release via p38 MAPK pathway activation, a phenomenon suppressed by SB203580, but not ERK inhibitors.…”
Section: Discussionmentioning
confidence: 99%